Cu(II)‐Catalysed Azide‐Alkyne Cycloaddition Reaction towards Synthesis of β‐Carboline C1‐Tethered 1, 2, 3‐Triazole Derivatives. Issue 16 (27th April 2021) - Kumar, Sunit; Malakar, Chandi C.; Singh, Virender
Abstract: Indole and β‐carboline alkaloids exhibit diverse range of significant pharmacological properties as reflected by their contribution in drug‐discovery. We have described the synthesis of hybrid molecules containing β‐carboline C1‐linked 1, 2, 3‐triazoles in moderate to good yields. The developed transformation was realized by using Cu(II)‐catalysed click‐reaction of diverse alkynes with in‐situ derived rarely explored β‐carboline tethered aliphatic azides. These molecular hybrids also exhibited excellent fluorescence properties. Abstract : A simple and efficient Cu(II)‐catalysed approach has been established towards the construction of biologically potential β‐carboline C1‐tethered 1, 2, 3‐triazole derivatives by using 1‐formyl β‐carboline (Kumujian C), commercially available substituted alkynes and sodium azide through click chemistry.